Mathematical thinking, self-regulated learning, and communication ability of Filipino and Japanese students a comparative study - Rocena, Lady Angela M.; Joaquin, Ma. Nympha B.; San Jose, Ronaldo M.; Oyzon, Maria Vanessa P. Lusung (Quezon City College of Education, University of the Philippines Diliman, 2019)
The present research investigated the mathematical thinking, self-regulated learning, and communication ability of Filipino and Japanese students. Specifically, this research sought to answer the following questions: (1) Do Filipino and Japanese students differ in terms of mathematical thinking, self-regulated learning, and communication ability; (2) Does mathematics self-regulated learning predict mathematical thinking; and (3) Does mathematical thinking predict mathematical communication ability? Analyses of the textbooks, samples tests, and classroom observations, as well as literature support for the results, were discussed as is their usefulness for improving mathematics teaching and learning.
Thesis
Includes bibliographical references (pages 163-174).
Keywords: Mathematics -- Study and teaching -- Philippines